Green Investment in the Islamic Capital Market: Opportunities and Challenges toward a Green Economy - Asri Jaya; A. Ifayani Haanurat; Nurlina, Nurlina; Vikram Singh (Universitas Muhammadiyah Makassar, 2026)
The escalating challenges of climate change, environmental degradation, and sustainability risks have intensified the demand for financial systems that facilitate the transition toward a green economy. Green investment has emerged as a core pillar of sustainable finance, with capital markets playing a crucial role in mobilizing long-term funding for environmentally responsible activities. Within this context, the Islamic capital market is considered to have strong normative alignment with sustainability principles due to its emphasis on ethics, justice, and accountability. However, existing research integrating green investment, Environmental, Social, and Governance (ESG) frameworks, and Islamic finance remains limited and fragmented. This study aims to systematically examine the opportunities and challenges of green investment within the Islamic capital market in supporting the green economy. Employing a Systematic Literature Review (SLR) approach, this study analyzes peer-reviewed journal articles published between 2015 and 2025. The findings reveal that the Islamic capital market holds significant potential to promote green investment through instruments such as green sukuk, ESG-oriented portfolios, and the integration of ESG with maqasid al-shariah principles. Nevertheless, several challenges persist, including the absence of standardized Sharia–ESG frameworks, divergence in ESG ratings, data quality limitations, and the risk of greenwashing. This study contributes to the literature by offering a comprehensive synthesis and providing policy and research implications to strengthen the role of Islamic capital markets in advancing a sustainable and inclusive green economy.